Tracking temporal variations of fatality and symptomology correlated with COVID-19 dominant variants and vaccine effectiveness in the United States - Shao Lin; Shao Lin; Han Liu; Quan Qi; Ian Trees; Donghong Gao; Samantha Friedman; Xiaobo Romeiko Xue; David Lawrence; David Lawrence (Frontiers Media S.A., 2024)
IntroductionWe described how COVID-19 fatality and symptoms varied by dominant variant and vaccination in the US.MethodsUsing the Restricted Access Dataset from the US CDC (1/1/2020-10/20/2022), we conducted a cross-sectional study assessing differences in COVID-19 deaths, severity indicators (hospitalization, ICU, pneumonia, abnormal X-ray, acute respiratory distress syndrome, mechanical ventilation) and 12 mild symptoms by dominant variant/vaccination periods using logistic regression after controlling for confounders.ResultsWe found the highest fatality during the dominant periods of Wild (4.6%) and Delta (3.4%). Most severe symptoms appeared when Delta was dominant (Rate range: 2.0-9.4%). Omicron was associated with higher mild symptoms than other variants. Vaccination showed consistent protection against death and severe symptoms for most variants (Risk Ratio range: 0.41-0.93). Boosters, especially the second, provided additional protection, reducing severe symptoms by over 50%.DiscussionThis dataset may serve as a useful tool to monitor temporospatial changes of fatality and symptom for case management and surveillance.